Properties of flexural and impact of matrix composites polyester reinforced with short lignocellulosic fibers (Research, Society and Development, 2022)
Composite materials stand out for enabling the development of new materials that are environmentally friendly, whose manufacturing processes and waste are increasingly less harmful, associated with good mechanical properties. In this context, this work sought to investigate the mechanical behavior in flexural and impact of polyester matrix composites with the inclusion of short fibers of sisal, piassava, raffia, mallow and jute arranged randomly. The mechanical properties of flexural were evaluated according to ASTM D 790 and the impact toughness Charpy with the ASTM D 6110 standard. The results showed that when subjected to flexural stresses, the composites presented resistance of 112 .12 MPa for the neat matrix and 35.21; 34.45; 27.29; 25.89 and 20.56 MPa with the inclusion of sisal, piassava, raffia, mallow and jute fibers, respectively. As for the impact test, they showed values of 31.50 kJ/m² for the neat matrix and 57.06; 52.52; 48.03; 38.02; 37.65 kJ/m² with the inclusion of sisal, piassava, raffia, mallow and jute fibers, respectively. Then, the fracture surface of the composites was analyzed with a microscope in order to correlate the fracture aspects with the mechanical properties.